Chemical composition and phagocyte immunomodulatory activity of Ferula iliensis essential oils. Issue 6 (3rd March 2017) - Oüzek, Gulmira; Schepetkin, Igor A.; Utegenova, Gulzhakhan A.; Kirpotina, Liliya N.; Andrei, Spencer R.; Oüzek, Temel; Baser, Kemal Huüsnuü Can; Abidkulova, Karime T.; Kushnarenko, Svetlana V.; Khlebnikov, Andrei I.; Damron, Derek S.; Quinn, Mark T.
Abstract : Activation of neutrophils by Ferula iliensis essential oils enriched in ( E / Z )‐propenyl sec‐butyl disulfides is mediated by activation of transient receptor potential V1 channels. Abstract : Essential oil extracts from Ferula iliensis have been used traditionally in Kazakhstan for treatment of inflammation and other illnesses. Because little is known about the biologic activity of these essential oils that contributes to their therapeutic properties, we analyzed their chemical composition and evaluated their phagocyte immunomodulatory activity. The main components of the extracted essential oils were ( E )‐propenyl sec ‐butyl disulfide (15.7–39.4%) and ( Z )‐propenyl sec ‐butyl disulfide (23.4–45.0%). Ferula essential oils stimulated [Ca 2+ ]i mobilization in human neutrophils and activated ROS production in human neutrophils and murine bone marrow phagocytes. Activation of human neutrophil [Ca 2+ ]i flux by Ferula essential oils was dose‐dependently inhibited by capsazepine, a TRPV1 channel antagonist, indicating that TRPV1 channels mediate this response. Furthermore, Ferula essential oils stimulated Ca 2+ influx in TRPV1 channel–transfected HEK293 cells and desensitized the capsaicin‐induced response in these cells. Additional molecular modeling with known TRPV1 channel agonists suggested that the active component is likely to be ( Z )‐propenyl sec ‐butyl disulfide. Our results provide a cellular and molecular basis to explain at least part of the beneficial therapeutic properties of FEOs.